A Case Study: The Effect of Visitors on Two Captive Pumas With Respect to the Time of the Day - Maia, Caroline M. [UNESP]; Volpato, Gilson Luiz [UNESP]; Santos, Eliana F. (Routledge Journals, Taylor & Francis Ltd, 2012)
This study analyzed the effects of noise levels and number of visitors on the behaviors of a mother puma and her daughter in a zoo environment with respect to the time of day. The study monitored visitation (noise and number) over two 1-week periods (4 weeks between periods) and frequency of various puma behaviors (videorecorded). The study analyzed videotaped behavior of the pumas based on the time of day and visitors number and noise levels. There was a direct association of puma behaviors with visitors number and noise levels. The daughter puma was the most affected and behavioral changes of both pumas correlated more strongly with the noise level than the number of visitors. The noise level and number of visitors affected the behavior of the mother and her daughter only in the morning. The results of this study indicate that both noise level and number of visitors affected these pumas but revealed the noise as predominant. Moreover, the response of these pumas to visitors depended on the time of the day.